2013
DOI: 10.1016/j.adolescence.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors and outcomes of loneliness trajectories from childhood to early adolescence

Abstract: Using latent class growth analysis, we were interested in investigating how experiences of loneliness emerge in distinct developmental patterns over the course of middle childhood and adolescence (NICHD Study of Early Child Care, N = 832). Second, we examined the role of demographic, mental health, and behavioral variables in association with these discrete patterns of loneliness. Loneliness was measured at 3 time points: age 9, age 11, and age 15. Results indicated five discrete trajectories of loneliness fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
165
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(197 citation statements)
references
References 46 publications
23
165
4
5
Order By: Relevance
“…Those whose loneliness remained chronically high or whose loneliness was moderately high and declined slightly over this time interval had significantly higher levels of depressive symptomatology at age 18, and the largest increases in depressive symptoms since age 12, than those who were consistently non-lonely, whose loneliness was stable and low, or who exhibited a steep decline in loneliness during this time [30]. Using a similar class-based approach to loneliness trajectories between age 7 and 15 in over 800 students, Schinka et al [31] found that those with a stable low trajectory had significantly lower levels of depressive symptoms at age 15 than those with a chronic or a high increasing trajectory, who in turn had higher depressive symptoms than those with a moderate increasing or a decreasing trajectory. Suicidal ideation followed a similar pattern of effects such that those with a chronic or high increasing loneliness trajectory were, respectively, approximately 11% and 7% more likely to have reported suicidal ideation at age 15 than those in the stable low trajectory.…”
Section: (C) Adolescence (13-17 Years)mentioning
confidence: 99%
“…Those whose loneliness remained chronically high or whose loneliness was moderately high and declined slightly over this time interval had significantly higher levels of depressive symptomatology at age 18, and the largest increases in depressive symptoms since age 12, than those who were consistently non-lonely, whose loneliness was stable and low, or who exhibited a steep decline in loneliness during this time [30]. Using a similar class-based approach to loneliness trajectories between age 7 and 15 in over 800 students, Schinka et al [31] found that those with a stable low trajectory had significantly lower levels of depressive symptoms at age 15 than those with a chronic or a high increasing trajectory, who in turn had higher depressive symptoms than those with a moderate increasing or a decreasing trajectory. Suicidal ideation followed a similar pattern of effects such that those with a chronic or high increasing loneliness trajectory were, respectively, approximately 11% and 7% more likely to have reported suicidal ideation at age 15 than those in the stable low trajectory.…”
Section: (C) Adolescence (13-17 Years)mentioning
confidence: 99%
“…These associations may be underpinned by the belief that engaging in sex is one way to reduce feelings of loneliness [20], with intimate connections possibly being seen as a way to counter social rejection [21]. Feeling lonely may also be connected with aggressive behaviour [22-24]. Specifically, being aggressive with peers may lead to worse relations and possibly subsequent rejection [23,24], although loneliness in childhood has also been found to be a precursor of later aggression in adolescence [22].…”
Section: Introductionmentioning
confidence: 99%
“…This subgroup consists of individuals who report persistent loneliness over many years and report feeling socially or emotionally distant from others. In several multiwave longitudinal studies, researchers investigating developmental trajectories of loneliness from childhood through early adulthood have indicated that between 3% and 22% of people experience prolonged loneliness (Benner, 2011;Harris, Qualter, & Robinson, 2013;JobeShields, Cohen, & Parra, 2011;Ladd & Ettekal, 2013;Qualter, Brown, et al, 2013;Schinka, Van Dulmen, Mata, Bossarte, & Swahn, 2013;Vanhalst, Rassart, et al, 2013). Further, despite a dearth of studies in which researchers investigated prolonged loneliness in middle adulthood, stability and change in loneliness among older adults have been investigated by researchers using retrospective and longitudinal designs.…”
Section: Sources Of Transient and Prolonged Feelings Of Loneliness Acmentioning
confidence: 99%
“…In addition, children who experience prolonged loneliness and who become increasingly withdrawn limit their opportunities to practice their social interaction skills, becoming more deficient in social skills over time (Schinka et al, 2013). Figure 1 shows how social withdrawal might work as part of RAM but also how it might lead to problems with reconnection.…”
Section: The Behavioral Reaffiliation Process Across Ontogenymentioning
confidence: 99%